EATING HABITS AND PHYSICAL EDUCATION AND SPORT- COMPONENTS OF YOUTH HEALTH EDUCATION - Cristian STANCIU; Ioan HĂȘMĂȘAN; Iulian STOIAN; Puiu Marcel POMOHACI; Virgil ENE-VOICULESCU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This paper provides an overview of the physical activity (PA) and dietary behaviour of college students, emphasizing the need for long-term education to lead a healthy life. Four research objectives were set, and an online study was carried out (N = 365, 65.21% women, 65.21% urban residence), using a self-administered questionnaire. The average age of the respondents was 20.34 years. The collected data was analysed, processed and interpreted accordingly with the help of tables and figures. The main results: in the families of 84.11% of those surveyed, a part of the necessary food needed is produced in the household. The main source of food supply is the hypermarket, the proportion with which the food is purchased from here varies depending on the product category: 65.48% other food products; 60.55% milk and dairy products; 46.58% meat and fish products; 46.03% bread and bakery products; 44.93 % fruits; 43.01% vegetables. The dietary habits indicate that 91.33% of young people include all food categories in their diet. Approx. 19% of the young adults have a hyperprotein diet, and 13.97%, a hypocaloric one. More than 90% of the subjects recognize the importance of physical education for human health, approximately 92% of them engage in walking as a form of PA, 41% work out in the gym, and 53.15% stated that they allocate between 1 and 5 hours for PA/week. The main motivation to practice different sports is the desire to stay healthy (score of 4.17), and the main benefit identified for their own health refers to the way they feel, full of energy (score 4.03). More than 70% of young people use digital applications to monitor the number of steps taken and PA. More than 2/3 of the study participants believe that it is important for physical education to be part of students' daily routine. Universities can generate societal change, giving young people the opportunity to adopt healthy eating habits and understand the importance of PA for both human and planetary well-being.